Description of core competencies in the conduct of health technology assessment in the Philippines - Jackarain, Faisal H.; Garcia, Jr., Fernando B. (Manila College of Public Health, University of the Philippines Manila, 2023)
Being a relatively new field in public health, disparity exists between high-income and low- and middle-income countries (LMICs) in terms of Health Technology Assessment (HTA) capacity (Whyte & Hall, 2013; Singer, 2008; Tarn et al, 2008). Among the seven challenges of HTA in LMICs identified by Bijlmakers et al (2017), three of these were related to health human resource capacity for HTA. These are (1) limitations in HTA capacity; (2) policy-making-related HTA processes not well-established; (3) limited engagement with HTA stakeholders. This study sought to answer the question "What are the core competencies (i.e., knowledge, skills, and attitudes) needed to gauge the readiness of health professionals in HTA?. Furthermore, this study aimed to identify which are basic and core competencies of public health professionals towards the conduct of HTA in the context of universal healthcare. A descriptive qualitative approach was used, inclusive of a (1) scoping review of HTA competencies in LMICs and (2) focus group discussions with HTA practitioners and decision-makers. In order to interpret the information obtained from the data collection process, this study utilized thematic analysis as its primary qualitative analysis method. The role of HTA in universal health care is currently evolving. To increase the number of human resources who shall conduct HTA, and improve the competencies of currently performing HTA practitioners, a competency inventory for HTA was derived and may serve as guide to create training programs, academic degree programs, or courses related to HTA in the Philippines.
Includes references and appendices.
Thesis
Keywords: Health technology assessment -- Philippines; Professional competence -- Philippines; Health planning -- Philippines